Monitoring of the infectious agent Chlamydia psittaci in common swifts (Apus apus) in the area of Hannover, Lower Saxony, Germany - W Tiyawattanaroj; R Lindenwald; L Mohr; E Günther; M Legler (Schlütersche Fachmedien GmbH, 2021)
The occurrence of the zoonotic pathogen Chlamydia (C.) psittaci in the common swift (Apus apus) with a high prevalence was reported in the literature. These long-distance migrant, which only consume aerial plankton, can reach high population densities in places with suitable breeding sites. Dedicated competent private individuals take part in the hand-rearing of juvenile common swifts in wildlife rescue centres, which unavoidably results in close contact with the avian patients. For this reason, we monitored the infectious agent C. psittaci in common swifts in the area of Hannover, Lower Saxony, Germany, from 2009 to 2018. Pooled organ samples (liver, spleen, kidney, lungs, trachea) of fatally injured swifts (n=243) were examined using real-time PCR. In conclusion, specific sequences of C. psittaci (examined in the years 2009–2018) as well as Chlamydia spp. (examined in the years 2016–2018) could not be detected in any common swift within the investigation period and the studied area. These results show that the common swift is unlikely to be a reservoir for the zoonotic agent C. psittaci in the Hannover area.